2000
DOI: 10.1002/j.1556-6676.2000.tb02571.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Mental Health Concerns of International Students

Abstract: International students on the American college campus are a diverse and increasing population whose unique concerns are traditionally overlooked. However, given the evidence that the demands for cultural adjustments frequently place international students at greater risk for various psychological problems than are students in general, it is important that sufficient and readily accessible mental health services be established for them. This article examines the sources of international students' psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

20
707
3
22

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 729 publications
(752 citation statements)
references
References 27 publications
20
707
3
22
Order By: Relevance
“…Some studies show that women may be more at risk for problems than males (Carballo, 1994). However, other studies show that international male students suffer higher levels of acculturative stress than females (Mori, 2000 Education is a consistent negative predictor of acculturative stress (Berry, 1997).…”
Section: Berry's Model For Acculturative Stressmentioning
confidence: 90%
See 4 more Smart Citations
“…Some studies show that women may be more at risk for problems than males (Carballo, 1994). However, other studies show that international male students suffer higher levels of acculturative stress than females (Mori, 2000 Education is a consistent negative predictor of acculturative stress (Berry, 1997).…”
Section: Berry's Model For Acculturative Stressmentioning
confidence: 90%
“…One way their parents' SES influences acculturation is reflected in financial support. Many studies have found that financial difficulty is an important stressor for international students (Lin & Yi, 1997;Liu, 2009;Mori, 2000;Pan et al, 2010). Their visa statuses limit their ability to apply for financial aid and employment opportunities (Thomas & Althen, 1989).…”
Section: Berry's Model For Acculturative Stressmentioning
confidence: 99%
See 3 more Smart Citations